Perancangan Kampanye Edukasi Pentingnya Self Reward Pada Perempuan Muslimah Usia 19-24 Tahun - Jian Fitriana; Aditya Rahman Yani; Masnuna Masnuna (Badan Penerbit STIEPARI Press, 2025)
Surabaya as one of the largest metropolitan cities in Indonesia, which often faces various complex social and economic challenges. One of them is the increasing number of suicide cases, which is a serious concern for local governments, communities, and mental health organizations. Suicide itself is an act of someone who deliberately ends their life. In the book Hygiene Mental released by Kartini Kartono, it is explained that suicide is one way to escape from the real world. This study uses a descriptive qualitative approach method. Qualitative research is research that examines the perspectives of participants with interactive and flexible strategies. The planning of this Self Reward educational campaign uses quantitative and qualitative methods. This second option was chosen because the design requires relevant data. To obtain more in-depth information about the phenomena found, data from the questionnaire alone is not enough, the quantitative method uses a questionnaire as a data collection technique, while the qualitative method uses observation and interviews. The design of this educational campaign uses an attractive and educational visual concept with a minimalist style, pastel colors, and illustrations that suit the character of Muslim women aged 19-24 years. The campaign targets active audiences on social media and Islamic self-development, through online media (Instagram) and offline (studies, workshops) to expand the reach of the message. The design of this educational campaign aims to increase awareness of Muslim women aged 19–24 years about the importance of self-reward as a form of positive, meaningful self-esteem, and in line with Islamic values. This campaign uses attractive visual and digital media to change negative views about self-reward, and encourage Muslim women to value themselves more in order to maintain their mental and emotional health.